Communication indicators for integrating diverse cultures in junior female residences at a South African tertiary institution - De Lange, Lucrezea; Mulder, Dalmé (Department of Communication Science, University of the Free State, 2012)
Residences are directly affected by transformational change in South Africa, as these are key areas in transformation strategies of South African tertiary institutions. Although inroads have been made in this area, there is still room for improvement as transformation targets seem difficult to reach. To address this problem, the primary objective of this study was to recommend a theoretical communication framework that can contribute towards more effective communication during the process of change in multicultural junior female residences. A qualitative approach and grounded theory strategy were used as research design. As the grand theory of this study is based on the general systems theory approach, the Mitroff model (Mitroff et al. 1974) of problem-solving was applied. As a holistic perspective is deemed essential in order for an organisation to change successfully, the four dimensions of a contemporary organisation impacted by change were explored. The importance of organisational culture, and the essential place of the learning organisation where constant development of employees is encouraged to ensure that the organisation survives in, and adapts to, an ever-changing environment were emphasised. The central role of the manager, the importance of leadership communication, the engaging of employees, as well as the fact that listening to employees should be regarded as an action step critical to successful change implementation were discussed. An important factor often overlooked, namely the human factor or micro-emotional level of the organisation, was addressed. A five-pillar communication framework with indicators that can contribute towards more effective communication during a change intervention was recommended.
Keywords: South Africa; Transformation; Tertiary education; Residences